PENGEMBANGAN DESAIN PEMBELAJARAN INQUIRY MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA MATERI LUAS DAN VOLUME BENDA PUTAR - Sulistyawati Sulistyawati (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
Learning strategy which gives less chance for the students to be actively included in the learning process will reduce the interest of students in learning which resulted in the lack of students’ motivation in learning which also will affect the students achievement in learning. The active learning strategy is a strategy which actively includes students to be active physically, mentally and socially. Based on these fact, the strategy of learning used by teacher plays a very important role in improving the students’ motivation as well as the success of learning. To achieve the goal of learning, teacher should pay attention to: (1) reduce the direct lecture method, (2) assigns different assignment to each students, (3) groups students based on their ability, (4) the material must be modified and enriched accordingly, (5) uses variation of procedures, (6) tries to develop the learning situation based on the students’ abilities, (7) motivate students to me actively engage in all learning activities. Inquiry Based Learning is an important component of constructivist approach which has a long history in innovative learning. Learning through inquiry will gives benefits for students. It spur on students’ interest to know more things, motivates them to continue learning to get the final answer. Students will learn to solve problem independently and think critically as they must analyzed and arrange information.